A multidimensional case study of English education and internationalisation policy planning in Japanese higher education: a socioeducational perspective - Higgins, Robert M. (2022)
The internationalisation of higher education is a trend that is pervasive across the world and in Japanese higher education this trend is inextricably linked to English education (Rose and McKinley, 2018). The factors that have contributed to English education acting as a primary driver for internationalisation in higher education in Japan reveal a complexity of issues that permeates across the societal, higher education sector, and institutional (campus/classroom) socioeducational spectrum of Japan. In this study, this socioeducational context was analysed from a multidimensional case study perspective (Bartlett and Vavrus, 2017b). This relates to the ways in which the different sets of data were compared and analysed from global, historical, vertical and horizonal perspectives. The horizontal focus was on the social practices of policy planning actors, such as teachers and students, contextualised in relation to the vertical structural activities of higher education institutions and governments. These practices and structures were placed in a global and historical perspective.